IBS - open building system for housing in Malaysia - Abdul Rahim, Asiah (s.n, 2012)
One major hurdle for research in the area of construction industrialization was to define the boundaries and establish clear basis of measurement. The terms used in construction industrialization are ill defined, often interchangeably with other terms and their precise definitions depend heavily on user's experience and understanding, which vary from country to country